Sugarcane‐Based Photothermal Materials for Efficient Solar Steam Generation. Issue 27 (17th July 2019) - Xiao, Chaohu; Chen, Lihua; Mu, Peng; Jia, Juan; Sun, Hanxue; Zhu, Zhaoqi; Liang, Weidong; Li, An
Abstract: Solar steam generation is a promising strategy for harvesting solar energy for diverse applications such as desalination and wastewater treatment. Here, we demonstrate the fabrication of polypyrrole modified sugarcane (PPy‐SC) as efficient photothermal material for solar steam generation. The PPy‐SC possesses various close‐packed open channels in horizontal plane and super hydrophilic wettability which is beneficial for rapid transportation of water molecules. In combination with its abundant porosity (47%), low apparent density (80 mg cm −3 ), low thermal conductivity (0.042 W m −1 K −1 ), and broad light absorption (90%). The prepared PPy‐SC exhibits a high evaporation rate of 1.59 kg m −2 h −1 and conversion efficiency of 90.6%, under 1 sun irradiation. In addition, the PPy‐SC also shows good performance in desalination. With the merits of low‐cost, eco‐friendly, simple fabrication process, high solar energy conversion efficiency, the PPy‐SC shows great potential as an efficient photothermal material for solar steam generation. Abstract : We demonstrate the simply fabrication of polypyrrole modified sugarcane (PPy‐SC) as efficient photothermal material for solar steam generation, the PPy‐SC possesses abundant porosity with close‐packed open channels in horizontal plane and highly developed honeycomb structure in longitudinal plane, low apparent density, broad light absorption, and low thermal conductivity, resulting in a high energy conversion efficiency of 85.3% under 1 sun irradiation.Therefore, the PPy‐SC has great potential for a wide range of large‐scale applications.